Effect of depressants on flotation separation of magnesite from dolomite and calcite - Qin, Wenqing; Hu, Junjie; Zhu, Hailing; Jiao, Fen; Jia, Wenhao; Han, Junwei; Chen, Chen (International journal of mining science and technology, 2023)
The flotation separation of magnesite from calcium-containing minerals has always been a difficult subject in minerals processing. This work studied the inhibition effects of carboxymethyl cellulose (CMC), sodium lignosulphonate, polyaspartic acid (PASP) and sodium silicate on flotation behaviors of magnesite, dolomite and calcite, providing guidance for the development of reagents in magnesite flotation. The micro-flotation results showed that among these four depressants, sodium silicate presented the strongest selectivity due to the highest recovery difference, and the flotation separation of magnesite from dolomite and calcite could be achieved by using sodium silicate as the depressant. Contact angle measurement indicated that the addition of sodium silicate caused the largest differences in surface wettability of the three minerals, which was in line with micro-flotation tests. Furthermore, zeta potential test, the Fourier transform infrared (FT-IR) spectroscopy and atomic force microscope (AFM) imaging were used to reveal the inhibition mechanism of sodium silicate. The results indicated that the dominated component SiO(OH)3− of sodium silicate could adsorb on minerals surfaces, and the adsorption of sodium silicate hardly affected the adsorption of NaOL on magnesite surface, but caused the reduction of NaOL adsorption on dolomite and calcite surfaces, thereby increasing the flotation selectivity.